Factors influencing the sporting attitude among excellent students / Siti Nazariah Abdul Razak, Tajul Arifin Muhamad and Wan Rezawana Wan Daud - Abdul Razak, Siti Nazariah; Muhamad, Tajul Arifin; Wan Daud, Wan Rezawana (Universiti Teknologi MARA, 2022)
Physical sporting activities is beneficial for your health. It has to be continuously and constantly performed route in creating positive and healthy lifestyle as it involves self-discipline. It needs a special interest and a positive mindset to attract students to take up sporting activities. The objective of this study is to assess the students' interest in sports based on several factors among the excellent students. The samples for this study are a group of students (N = 420) comprises of male (n = 210) and female (n = 210) with the age of 16 years old, selected based on simple random sampling. Questionnaire forms were used as a method for data collection. Descriptive and inferential analysis was used to look at the factors influencing students' sporting attitudes based on demographic data. The result shows that there are four factors highly influencing sporting attitudes. However, only the aspect of value that has significance different from gender p <0.05, where male students are higher than female. Nevertheless, the most significant factor is gender, p<0.05, where male students found to be higher than female. This value aspect is a preliminary consideration of the advantages or disadvantages of sports. Sporting assessment also depends on the effectiveness of teaching by educators who shape the behavior of students to pick up sports. Hsiao (2009) emphasizes the attitude of teachers or lecturers who care about students, know what is being taught, easy to discuss and make teachers and lecturers happy to be with them.